On the control of Phyllocnistis citrella Stainton (Lepidoptera Gracillariidae) by selective insecticides and by manipulation of indigenous natural antagonists (Bollettino di zoologia agraria e bachicoltura, 2024)
A field trial looking at the efficacy of selective chemicals and biological procedures against the Citrus leaf miner (CLM) in a new plantation of citrus lemon, 14 Ha in extent, including about 3 years old plants, was carried out in Sicily. The citrus grave made of 3836 trees was divided into four blocks, one of which was treated with methomyl, one with paraffin-oil, one with imidacloprid and another one with inoculative releases either of Cirrospilus diallus (Walker) or C. pictus (Nees), emerged from parasitized larvae of CLM collected in the field and bred in climatic room. The final efficiency of the different procedures was measured by the percentage (in cm2) of necrotized leaf surface due to the CLM larval trophic activity both on the sprayed and on the unsprayed plants. Results concerning various pest management procedures are discussed.
Keywords: Phyllocnistis citrella; Citrus lemon young plantation; cultural biological and chemical control procedures